Sussing out sustainability: The case of Singapore's property developers - HWANG, Soo Chiat (Institutional Knowledge at Singapore Management University, 2013)
The case is set in June 2013, and deals with a small to medium-sized Singapore-based property developer’s decision on whether to launch a sustainability initiative and engage in sustainability reporting as an innovative practice to improve the long run viability of the company through improved operational efficiencies. The question arose off the back of the 2008 financial crisis and subsequent recession with which the adoption of sustainability by large property developers in Singapore coincided, and which proved the vulnerability of the property development industry to macro-economic effects. Top management at the company had tasked Annie Tan, the company's COO, to render an initial critical evaluation of the competitors' sustainability initiatives and sustainability reporting, before making recommendations on the adoption and design of a sustainability initiative and sustainability reporting for the privately held property developer that specialised in small-scale customised property developments. The case discusses the current practice of sustainability initiatives and sustainability reporting, reviews dimensions of sustainability, notably the triple bottom line of environmental, social and economic sustainability as well as sustainability measures and metrics as they relate to effectiveness and efficiency, and assessed the correlation and causality in the relationship between sustainability, productivity and profitability.